Guillain-Barre Syndrome Presenting With Bilateral Facial Nerve Palsy - INALOO, Soroor; KATIBEH*, Pegah (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Inaloo S, Katibeh P. Guillain-Barre Syndrome Presenting With Bilateral Facial Nerve Palsy. Iran J Child Neurol. 2014 Winter;8(1):69-71. Objective This case study is about an 11-year-old girl with bilateral facial weakness, abnormal taste sensation, and deep tendon reflexes of both knees and ankles were absent. However, the muscle power of the lower and upper extremities across all muscle groups was normal. After 2 days, she developed paresthesia and numbness in the lower extremities. Other neurologic examinations, such as fundoscopic evaluation of the retina were normal with the muscle power of both upper- and lower-extremities intact. A lumbar puncture revealed albumincytological dissociation. EMG and NCV were in favor of Guillain-Barre syndrome, for which IVIG was prescribed and the abnormal sensations in the lower limbs rapidly improved. Bilateral facial diplegia without weakness and paresthesia is a variant of Guillain-Barre syndrome that mostly presents with acute onset, rapid progression with or without limb weakness, paresthesia, and decreased or absent DTR and albumin-cytological dissociation. References: Barbi F, Ariatti A, Funakoshi K, Meacci M, Odaka M, Galassi G. Parvovirus B19 infection antedating Guillain-Barre’ syndrome variant with prominent facial diplegia. J Neurol 2011 Aug; 258(8):1551-2. doi: 10.1007/s00415-011-5949-5. Epub 2011 Feb 15. Yardimci N, Avci AY, Kayhan E, Benli S. Bilateral facial nerve enhancement demonstrated by magnetic resonance imaging in Guillain-Barré syndrome. Neurol Sci 2009 Oct; 30(5):431-3. doi:10.1007/s10072-009-0120-0. Lim TC, Yeo WS, Loke KY, Quek SC. Bilateral facial nerve palsy in Kawasaki disease. Ann Acad Med Singapore 2009; 38(8):737-8. Quintas E, Silva A, Sarmento A. Bilateral facial palsy in a young patient after meningococcal meningitis, associated to herpetic infection. Arq Neuro-Psiquiatr 2009; 67(3a): 712-14. Jain V, Deshmukh A, Gollomp S. Bilateral facial paralysis: case presentation and discussion of differential diagnosis. J Gen Intern Med 2006; 21(7):C7-10. Kamaratos A, Kokkoris S, Protopsaltis J, Agorgianitis D, Koumpoulis H, Lentzas J et al. Simultaneous Bilateral Facial Palsy in a Diabetic Patient. Diabetes Care 2004; 27 (2): 623-24. Magliocca KR, Leung EM, Desmond JS. Parotid swelling and facial nerve palsy: an uncommon presentation of sarcoidosis. Gen Dent 2009; 57(2):180-2. Atsumi M, Kitaguchi M, Nishikawa S, Susuki K. A variant of Guillain-Barré syndrome with prominent bilateral peripheral facial nerve palsy-facial diplegia and paresthesias. Rinsho Shinkeigaku 2004 Aug; 44(8):549-52. Narayanan RP, James N, Ramachandran K, Jaramillo MJ. Guillain-Barré Syndrome presenting with bilateral facial nerve paralysis: a case report. Cases J 2008 Dec 8;1(1):379. Azarisman SMS, Shahrin TCA, Marzuki AO, Fatnoon NNA, Rathor MY. Bilateral facial nerve palsy secondary to an atypical presentation of Guillain-Barré syndrome. IMJ 2009; 8(1):41-4. Sethi NK, Torgovnick J, Arsura E, Johnston A, Buescher E. Facial diplegia with hyperreflexia--a mild Guillain-Barre Syndrome variant, to treat or not to treat? J Brachial Plex Peripher Nerve Inj 2007; 10(2):9. Burina A, Sinanović O, Smajlović D, Vidovic. Bilateral Oculomotor Nerve Palsy in Guillain-barre Syndrome. Med Arh 2008; 62 (2):119-120. Verma R, Chaudhari TS, Giri P. Unilateral facial palsy in Guillain-Barre syndrome (GBS): a rare occurrence. BMJ Case Rep 2012 Oct 19; 2012. pii: bcr2012007077. doi: 10.1136/bcr-2012-007077. Susuki K, Koga M, Hirata K, Isogai E, Yuki N.A Guillain-Barré syndrome variant with prominent facial diplegia. J Neurol 2009; 256(11): 1899-1905.